Role of protein carbonylation in diabetes - Hecker, Markus; Wagner, Andreas H. (Journal of inherited metabolic disease, 2018)
Diabetes mellitus is a metabolic disease characterized by, among others, elevated blood glucose levels. Hyperglycaemia as well as enhanced levels of glucosederived reactive metabolites contribute to the development of diabetic complications partly via increased generation of reactive oxygen species (ROS). ROS are not only part of signaling pathways themselves but also lead to carbonylation of particular amino acid side chains by direct metal-catalyzed oxidation. In addition, carbonyl groups can be introduced into proteins indirectly by non-oxidative covalent adduction of reactive carbonyl species generated by the oxidation of lipids or carbohydrates. Both direct and indirect carbonylation mechanisms may affect protein conformation, activity, and function. Herein we introduce the different mechanisms of the carbonylation reaction, discuss degradation mechanisms, and the fate of proteins modified this way and how the overall degree of carbonylation affects protein homeostasis and function differently. The role of protein carbonylation in metabolic control systems and cell signaling are also summarized. Finally, current diagnostic and antioxidant therapeutic options in diabetes are discussed.